2016
DOI: 10.1038/srep32511
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based proteomic analysis of plasma reveals abnormalities in lipid metabolism proteins in chronic kidney disease-related atherosclerosis

Abstract: Patients with chronic kidney disease (CKD) have a considerably higher risk of death due to cardiovascular causes. Using an iTRAQ MS/MS approach, we investigated the alterations in plasma protein accumulation in patients with CKD and classical cardiovascular disease (CVD) without CKD. The proteomic analysis led to the identification of 130 differentially expressed proteins among CVD and CKD patients and healthy volunteers. Bioinformatics analysis revealed that 29 differentially expressed proteins were involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…Our results correlate well with the data obtained by other researchers in that blood APOA4, AAT, VIL1, complement component and cytokine concentrations increased in patients with renal disorders [8,[11][12][13][14]28,[32][33][34]43,[69][70][71]. Moreover, we found elevated serum concentrations of potential oncomarkers (CUL5, antigen KI-67) and other intracellular proteins (NKRF, CAPRI, IGSF22, APPBP2, CCD171 and CCD43) in patients with CKD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results correlate well with the data obtained by other researchers in that blood APOA4, AAT, VIL1, complement component and cytokine concentrations increased in patients with renal disorders [8,[11][12][13][14]28,[32][33][34]43,[69][70][71]. Moreover, we found elevated serum concentrations of potential oncomarkers (CUL5, antigen KI-67) and other intracellular proteins (NKRF, CAPRI, IGSF22, APPBP2, CCD171 and CCD43) in patients with CKD.…”
Section: Discussionsupporting
confidence: 92%
“…The disadvantage of this method is its poor effectiveness in diagnosing early CKD. There are a number of studies where potential protein biomarkers of CKD were proposed and evaluated in the serum or plasma of patients [7,8,[11][12][13][14]. Peptide biomarkers can also provide insight into CKD diagnosis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Florens et al studied non-diabetic HD patients and found that 10 proteins were significantly upregulated (UDP-glucose: glycoprotein glucosyltransferase 1; β-2-microglobulin; SP-B; AMBP; insulin-like growth factor II; immunoglobulin heavy constant alpha 2; immunoglobulin lambda constant 2; HLA class I histocompatibility antigen; B-58 alpha chain; complement factor D; and inter-alpha-trypsin inhibitor heavy chain H1) and nine downregulated (guanylin; calpain-1 catalytic subunit; keratin, type I cytoskeletal 16; Ras-related protein Rab-6B; ganglioside GM2 activator; prostaglandin-H2 D-isomerase; secretoglobin family 3A member; thioredoxin-dependent peroxide reductase, mitochondrial; and solute carrier family 2, facilitated glucose transporter member 2) in HDL from HD patients compared to controls; these proteins are involved in lipid metabolism, hemostasis, wound healing, oxidative stress, and apoptosis pathways [ 71 ]. ITRAC (Isobaric Tag for relative and absolute quantitation)-based proteomics analysis also showed that the HDL proteome is remodeled in CKD, namely in ESRD patients under dialysis treatment [ 72 ]. Based on all these data, a schematic view of the major changes that occur in HDL composition in CKD, especially in ESRD patients, favoring dysfunctionality of HDL, is presented in Figure 2 .…”
Section: The Concept Of Hdl Dysfunctionality In Ckdmentioning
confidence: 99%
“…By extracting and analyzing these PRM spectrum files, quantitative information of the protein can be obtained. By extracting and analyzing these PRM spectrum files, quantitative information of the protein can be obtained [61,62].…”
Section: Prm Quantitation Analysismentioning
confidence: 99%